REFORMS AND THEIR IMPORTANCE IN THE DEVELOPMENT OF MUSEOLOGY IN DEVELOPING UZBEKISTAN - Mingboyeva Nozima Ulugbekovna; Talibjonova Zilola Khalimjan daughter (American Journals Publishing, 2024)
This article aims to support the activities of museums in our Country, complex development of their marketing policy and services sphere, effective application of innovative technologies to museums, as well as to create modern new expositions on the history of Uzbek people and statehood in museums, the first and Second Renaissance periods, the life and work of great allomas, to widely promote our rich historical and cultural heritage.
Keywords: Museum Foundation, culture, enlightenment, nature monuments, ”strategy of action”, ”on the organization of the Museum of Olympic glory”, our ancestors have a high level of knowledge and thinking, worldview, art, skill, talent.